Do Refugees Impact Voting Behavior in the Host Country? Evidence from Syrian Refugee Inflows in Turkey - Onur Altindag; Neeraj Kaushal (Institute of Labor Economics (IZA), 2017)
We study the effect of an influx of approximately three million Syrian refugees on voting behavior in Turkey. We use a difference-in-differences approach, comparing the political outcomes in geographic areas with high and low intensity of refugee presence before and after the beginning of Syrian civil war. To address the endogeneity in refugees' location choices, we adopt an instrumental variables approach that relies on the historic dispersion of Arabic speakers across Turkish provinces, taking advantage of the fact that Syrians are more likely to settle in locations with high Arabic-speaking host populations. We document a strong polarization in attitudes towards refugees between the supporters and opponents of the ruling Justice and Development party (AKP). Regression analyses of monthly survey data, however, suggest that the massive inflow of refugees induced only a modest drop in support for the AKP. We show similarly small, but statistically insignificant impact on actual election outcomes.
Keywords: F22; 330; attitudes towards refugees; voting behavior in Turkey; Syrian refugees